Anti-diabetic potential of ‘Safūf-i-Dhayābītus’ as standalone and as an adjuvant with glibenclamide in streptozotocin-induced diabetic rats - Nasir, Abu; Ansari, Athar Parvez; Rafeeqi, Towseef Amin; Goswami, Pankaj; Wadud, Abdul; Akbar, Seema; Ansari, Huzaifa (Phytomedicine Plus : International journal of phytotherapy and phytopharmacology, 2022)
Presently, Diabetes mellitus (DM) is categorized as an epidemic disease due to its high prevalence of mortality rate and morbidity, and is also considered as the main threat to the global population. Synthetic drugs used alone for the treatment of DM cause serious adverse effects and insufficiently minimize diabetic complications. Meanwhile, the use of herbal drugs as standalone or along with synthetic drugs is quite common. Hence, the present study was carried out to evaluate the antidiabetic effects of Safūf-i-Dhayābītus as standalone and along with glibenclamide in streptozotocin-induced diabetic rats. In this study, a total of 30 albino Wistar rats of 150–200 g b. w. were randomly divided into 5 groups of 6 animals each. Diabetes was induced in all groups except in group I by administering a single dose of streptozotocin (STZ) at 55 mg/ kg b. w. Group I served as plain control while group II as disease control. Group III was treated with glibenclamide at 0.6 mg/ kg. b. w. and served as standard control while group IV received Safūf-i-Dhayābītus at 500 mg/ kg b. w. and served as test group A. Group V administered Safūf-i-Dhayābītus at 500 mg/ kg b. w. along with glibenclamide at 0.6 mg/ kg b. w. for 21 days. The FBS of rats above 250 mg/ dl was considered as diabetic, tested after induction of DM. The biochemical parameters such as FBS, ALP, TBR, SGOT, SGPT, blood urea and serum creatinine, total cholesterol and triglyceride; and histopathological examination of the liver and kidney specimens were carried out at the end of the study. The FBG, ALP, SGPT levels in test group B were reduced significantly as compared to that of standard control, and test group A. The SGOT, TBR and b. urea levels in test groups A & B were significantly reduced as compared to that of standard control. The s. creatinine level in test groups A & B, and standard control was significantly reduced as compared to that of disease control. The total cholesterol level in test groups A & B was promisingly decreased as compared to the standard control. Histopathological studies of the liver and kidney specimens of the rats belonging to test groups A & B reduced hepato-nephrotoxicities in diabetic rats. The present study revealed that Safūf-i-Dhayābītus as standalone and in combination with glibenclamide possesses significant hypoglycaemic, hepatoprotective, nephroprotective and hypocholesterolemic effects in STZ-induced diabetic rats. [Display omitted]